Boosting energy for enhanced performance - Hamilton, A.; Lawson, T.; Shepherd, J. (Peak Performance, 2008)
A new workbook that gives you the essential competitive edge over all those other athletes who: * Don`t properly understand the correct role of sleep in enhancing recovery - so are never at their best… * Don`t know the best times of the day for high-intensity training - so don`t get top results… * Incorrectly calculate their necessary food intake - and thereby undermine their sports performance… Chronobiology: Your circadian rhythm, or body clock, is introduced with all the training and performance implications explained (Andrew Hamilton) Sleep Physiology: The importance of quality and quantity of sleep for athletic performance is illustrated (Tim Lawson) Energy Metabolism: Misconceptions on lactate and its effect on energy are condemned and corrected (John Shepherd) Rest and Recovery: The lasting physiological effects of exercise can help optimise performance and recovery once understood (John Shepherd) Nutrition: Our man cycles the Alpe d`Huez stage of the Tour de France to try and comprehend the energy levels and nutritional requirements (Tim Lawson)